Viscosity Results for a Class of Evolution Inclusions with Maximal Monotone Operators. (4th April 2018) - Saïdi, Soumia; Yarou, Mustapha Fateh
ABSTRACT: In the finite dimensional setting, we investigate the existence of viscosity subsolutions of Hamilton–Jacobi–Bellman equations related to control problems subject to evolution inclusions governed by time-dependent maximal monotone operators with Young measures.